2014
DOI: 10.1063/1.4866965
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of perpendicular magnetic anisotropy and transmission of spin-Hall-effect-induced spin currents by a Hf spacer layer in W/Hf/CoFeB/MgO layer structures

Abstract: We report that strong perpendicular magnetic anisotropy of the ferromagnetic layer in a W/CoFeB/MgO multilayer structure can be established by inserting a Hf layer as thin as 0.25 nm between the W and CoFeB layers. The Hf spacer also allows transmission of spin currents generated by an in-plane charge current in the W layer to apply strong spin torque on the CoFeB, thereby enabling current-driven magnetic switching. The antidamping-like and field-like components of the spin torque exerted on a 1 nm CoFeB layer… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

12
187
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 231 publications
(201 citation statements)
references
References 32 publications
12
187
2
Order By: Relevance
“…However, at finite t s , the STT also acquires a field-like component 4 . Experiments in W/Hf/CoFeB structures confirmed the presence of the SHE-based mechanism in the observed torques and showed that the SHE-STT can have both antidamping-like and field-like components of comparable magnitudes 27 .…”
mentioning
confidence: 69%
“…However, at finite t s , the STT also acquires a field-like component 4 . Experiments in W/Hf/CoFeB structures confirmed the presence of the SHE-based mechanism in the observed torques and showed that the SHE-STT can have both antidamping-like and field-like components of comparable magnitudes 27 .…”
mentioning
confidence: 69%
“…Moreover, as the perpendicular magnetic anisotropy field (H 0 an ) is also one of the key parameters in SOT systems with perpendicular magnetic anisotropy (PMA), so far, considerable research efforts have also been devoted to obtain an enhanced H 0 an to improve the thermal stability of spintronic devices [15,16], such as engineering the interface quality [17,18,19], changing identified SOC materials [16], and utilizing different post processing methods [20]. In a word, all these reports with views are not only to increase the magnitude of θ SH , but also to enhance the PMA.…”
Section: Introductionmentioning
confidence: 99%
“…SOTs have been identified and quantified by a variety of techniques including spin-torque ferromagnetic resonance [2,7,14,17,19,25], quasistatic magnetization tilting probed through harmonic voltage measurements [6,[8][9][10][11][12][13]17,[19][20][21][22][23][24][25][26]28,31], and current-induced hysteresis loop shift measurements [18,32,33]. Most studies of SOTs have focused on ultrathin metallic ferromagnet/heavy-metal bilayers with interfacial perpendicular magnetic anisotropy (PMA) [1][2][3][5][6][7][8][9][11][12][13][15][16][17][18][19][20][21][22][23][24][25]…”
mentioning
confidence: 99%
“…SOTs with both a fieldlike and dampinglike character can manifest in such systems, with the latter capable of driving magnetization switching [1][2][3][4][5]7,9,[11][12][13]15,21,22,24] and magnetic domain wall motion [26][27][28][29][30][31]. SOTs have been identified and quantified by a variety of techniques including spin-torque ferromagnetic resonance [2,7,14,17,19,25], quasistatic magnetization tilting probed through harmonic voltage measurements [6,[8][9][10][11][12][13]17,[19][20][21][22][23][24][25][26]28,31], and current-induced hysteresis loop shift measurements [18,32,33]. Most studies of SOTs have focused on ultrathin metallic ferromagnet/heavy-metal bilayers with interfacial perpendicular magnetic ani...…”
mentioning
confidence: 99%